Older adults physically inactive in occupational and commuting domains have a higher risk for osteopenia and osteoporosis: A 12-month prospective study - Dos Santos, Vanessa Ribeiro [UNESP]; Silva, Bruna Spolador de Alencar [UNESP]; Agostinete, Ricardo Ribeiro [UNESP]; Batista, Vitor Cabrera [UNESP]; Gobbo, Luís Alberto [UNESP] (Springer Nature, 2023)
Summary : The relationship between different domains of physical activity (PA) and bone health in older adults needs to be further investigated. We evaluated 379 Brazilian older adults and observed that the risk of osteopenia is higher in older adults who are physically inactive in occupational domain and for osteoporosis the risk is higher in physically inactive in commuting domain and total habitual PA. Purpose: Bone mineral density (BMD) usually decreases with age, and the risk of osteometabolic diseases, such as osteopenia and osteoporosis, increases in older adults. PA is strictly related to BMD. However, the relationship between different domains of PA and bone health in older adults is still unclear, and needs to be further investigated, aiming at the implementation of preventative health measures for this population. Thus, the aim of the current study was to analyze the association between different domains of PA and the risk for osteopenia and osteoporosis in older adults in a 12-month follow-up. Methods: Prospective study that included 379 Brazilian community-dwelling older adults, aged ≥ 60 years (70 ± 7 years, 69% women). Areal bone mineral density (aBMD) total, proximal femur, and lumbar spine were measured by dual energy X-ray absorptiometry (DXA), and PA was self-reported. Binary logistic regression analysis and 95%CI were used to analyze the association between the practice of PA in different domains (at baseline and follow-up) and risk for osteopenia and osteoporosis (follow-up). Results: The risk for osteopenia (total proximal femur or lumbar spine) is higher in older adults who are physically inactive in the occupational domain (OR:3.25; 95%CI:1.24–8.55). In addition, older adults who are physically inactive in the commuting domain (OR:3.43; 95%CI:1.09–10.82) and total PA (OR:5.58; 95%CI:1.57–19.88) present a higher risk for osteoporosis (total proximal femur or lumbar spine) compared to physically active older adults. Conclusion: The risk of osteopenia is higher in older adults who are physically inactive in occupational domain and for osteoporosis the risk is higher in physically inactive in commuting domain and total habitual PA.
Keywords: Aging; Exercise; Musculoskeletal health; Physical activity assessment